Iron (oxyhydr)oxides are responsible for the stabilization of Cu and Zn in AMD after treatment with limestone - Ding,Yuan; Long,Yan; Wang,Weiya; Wei,Zhe; Cai,Shuo (PeerJ, 2023)
The formation and transformation of secondary iron (oxyhydr)oxides and their role in the stabilization of copper (Cu) and zinc (Zn) in acid mine drainage (AMD) after limestone treatment are worth studying to better understand the impacts of limestone AMD treatment. In this study, the wastewater from a copper mine ditch was sampled. Two different doses of limestone (S: 5.33 g L−1 and SS: 8.00 g L−1) were applied to adjust the pH range of the sampled AMD. The concentrations of Fe, Cu and Zn in the supernatant and the levels of iron (oxyhydr)oxides and heavy metals in AMD sediments were dynamically monitored for 300 days to analyze the transformation of the secondary iron mineral phase and the role iron (oxyhydr)oxides play in the removal and stabilization of Cu and Zn. The results showed that the pH rose rapidly to 6.82, decreased to 5.82 on the 150th day, and finally decreased to approximately 4.63 by the 300th day, when the dosage of limestone (S) was 5.33 g L−1. Goethite was the main form of iron oxides in the sediments. As the incubation time increased, so did the content of crystalline Fe (oxyhydr)oxides. In addition, the Cu and Zn content in the fraction of crystalline Fe (oxyhydr)oxides increased as the corresponding iron (oxyhydr)oxide increased. When the high dosage of limestone (8.00 g L−1 or SS) was applied, the pH remained at approximately at 7.46 during the whole period and goethite and lepidocrocite were present in the sediment. Amorphous/ poorly crystalline Fe-oxyhydroxide was the main product after SS limestone dosage, indicating that the risk of Cu and Zn reactivation in the sediment was higher with a higher limestone treatment dosage.
Keywords: AMD; Neutralization; Iron (oxyhydr)oxide; Heavy metals; Stabilization mechanism